COLLECTIVE ETHNOGRAPHY OF PRINT MAKING IN YOGYAKARTA: A THEORETICAL STUDY OF ART AND SOCIETY - Wirajati, Yohanes De Britto; Waryanti, Dessy Rachma (Acintya, 2024)
The research entitled ‘Ethnography of Graphic Printmaking Collective in Yogyakarta: A Theoretical Study of Art and Society’ aims to analyse the institutionalisation process of two graphic print art collectives in Yogayakarta, namely: Grafis Minggiran and Krack! Printmaking Studio, and its influence on the art scene. The method that will be used in this research is ethnographic method with data collection techniques in the form of interviews and literature studies. This method was chosen in order to obtain a detailed depth of data from the experiences of the two graphic printmaking collectives. The results of this research are: (1) Both printmaking collectives endeavour to respond to art conventions (especially about techniques) in their art practices; (2) The formation of the collective is an on-campus tradition that spreads out; (3) Krack! Printmaking consistently makes the screen printing technique as a medium of expression in the realm of graphic printing art; (4) Krack! Printmaking then made the phrase ‘Ojo Wedi Mbleset’ (‘Don't be afraid to miss’) as their credo in carrying out the practice of silk screen/screen printing; (5) Grafis Minggiran makes the introduction of a wealth of techniques as its vision in art; (6) Grafis Minggiran is known as one of the (non-campus) graphic collectives that emerged the earliest and at the same time the initiator of the Yogyakarta Graphic Arts Week event.